HUBUNGAN ANTARA IMEJ KORPORAT USAHAWAN MUSLIM DAN PEMBAYARAN ZAKAT PERNIAGAAN DI DAERAH SEPANG, SELANGOR: The Relationship between Corporate Image of Muslim Entrepreneurs and Business ZakÄh Payment in Sepang, Selangor - Wahid, Hairunnizam; Abu Bakar, Abdul Halim; Ahmad, Sanep (Jurnal Syariah, 2017)
This study reveals that the awareness on the obligation to pay zakāh business among the Muslim entrepreneurs is still marginal. This study hypothesizes that the motivation of paying zakāh business among the Muslim entrepreneurs has a strong connection with their tendency to promote their business and corporate image. Interestingly, the Muslim entrepreneurs were interested to share their action in paying zakāh as the way to market their product or organization that finally will increase their profit. Therefore, this factor has been considered as an important factor that would potentially increase the amount of zakāh collected by Lembaga Zakat Selangor (LZS) every year. Thus, this study aims to analyze the factor of corporate image and other potential variables that probably influence the payment of zakāh business among the Muslim entrepreneurs in Sepang, Selangor. This study has studied several factors that potentially influencing the awareness of paying zakāh business including entrepreneur attitudes, corporate image, and zakāh’s service provided by the zakāh institutions, the staff of the zakāh institutions and also the fatwā of zakāh using logistic regression. The result shows that the variable of corporate image through paying zakāh business is an important and significant factor that motivates the Muslim entrepreneurs to pay zakāh. However the study shows that corporate image has a negative relationship with motivation of paying zakāh business. Several recommendations have been discussed in this study.